TMJ Ankylosis: A Reveiw - Ethena Priyadarsani (Indian Journal of Forensic Medicine & Toxicology, 2020)
Temporomandibular joint (TMJ) ankylosis is a pathologic condition where the mandiblar fusion takes placeto the fossa by bony or fibrous tissues. It interferes with normal day to day activities such as mastication,speech, oral hygiene, etc. Trauma to the chin is the most common factor of TMJ ankylosis followed byinfections. This article highlights the eitiology, clinical features, various classifications radiographic features,histopathological features and surgical management of TMJ ankylosis